The Attitude of Junior High School Students toward The Early Marriage - Tatarini Ika Pipitcahyani; Iiv Hayyu Chahyaya (Health Notions, 2018)
Early marriage in Indonesia reaches 50 million of the total population of 237.6 million people. The phenomenon of early marriage in other areas is not much different considering the fact that sexual behaviors of teenagers who have pre-marital sex often leads to early marriage. This attitude can be seen from early marriage to both women and men in general, marriage is more common in women than in men before they are 19 years old. So the adolescent prevention solution should know and understand about the dangers and losses of early marriage. Understand or not, can be known from the attitude of teenagers themselves in dealing with early marriage. The purpose of this research is to know the differences of attitude between young men and women about early marriage in PGRI 04 Bantur Junior High School, using a comparative design. The population was all students of grade 2 and 3 (89 students) in Junior High School of PGRI 04 Bantur, Malang, Indonesia. The sample size were 73 students (39 were male students and 34 were female students). The sampling technique was stratified random sampling. Data were collected by questionnaire then analyzed by Chi square test. The result of this research shows that young men had favorable attitude were 13 (33.3%) and unfavorable attitude were 26 (66.7%). While young women had favorable attitude were 26 (76.5%) and unfavorable attitude were 8 (23.5%). The p-value of Chi square test was 0.000 (there was difference attitude between young men and women toward early marriage). Keywords: Attitude, Early Marriage, Adolescent